Right ventrolateral and left dorsolateral 10 Hz transcranial magnetic stimulation as an add-on treatment for bipolar I and II depression: a double-blind, randomised, three-arm, sham-controlled study - Novák, Tomáš; Kostýlková, Lenka; Bareš, Martin; Renková, Veronika; Hejzlar, Martin; Renka, Jiří; Baumann, Silvie; Laskov, Olga; Klírová, Monika (The world journal of biological psychiatry, 2024)
OBJECTIVES: Despite the clinical importance of bipolar depression (BDE), effective treatment options are still limited. Transcranial magnetic stimulation (rTMS) has proven of moderate efficacy in major depression, but the evidence remains inconclusive for BDE. METHODS: A 4-week, double-blind, randomised, parallel-group, sham-controlled study (trial ID ISRCTN77188420) explored the benefits of 10 Hz MRI-guided right ventrolateral (RVL) rTMS and left dorsolateral (LDL) rTMS as add-on treatments for BDE. Outcome measures included changes in the Montgomery-Åsberg Depression Rating Scale (MADRS) score, self-assessment, response and remission rates, and side effects. RESULTS: Sixty patients were randomly assigned to study groups, and forty-six completed the double-blind phase. The mean change from baseline to Week 4 in MADRS was greater in both active groups compared to the sham, yet differences did not achieve significance (RVL vs sham: -4.50, 95%CI -10.63 to 1.64, p = 0.3; LDL vs sham: -4.07, 95%CI -10.24 to 2.10, p = 0.4). None of the other outcome measures yielded significant results. CONCLUSIONS: While not demonstrating the superiority of either 10 Hz rTMS over sham, with the limited sample size, we can not rule out a moderate yet clinically meaningful effect. Further well-powered studies are essential to elucidate the role of rTMS in managing BDE.
Keywords: dospělí; Bipolar Disorder; Female; bipolární porucha; kombinovaná terapie; Adult; výsledek terapie; ženské pohlaví; transkraniální magnetická stimulace; lidé; dvojitá slepá metoda; Treatment Outcome; Double-Blind Method; Male; Combined Modality Therapy; psychiatrické posuzovací škály; Transcranial Magnetic Stimulation; lidé středního věku; mužské pohlaví; Middle Aged; Psychiatric Status Rating Scales; Humans